Waste pickers in the Global South: understanding the key features that underpin the dominance of informality - Nicolás Labra Cataldo; Alejandro Gallego-Schmid; Carly McLachlan (Sustainability: Science, Practice, & Policy)
E-waste management in the Global South relies heavily on the informal sector. The associated workforce, vast in number, faces exposure to harmful substances and often represents society’s most vulnerable segments. While the coexistence of formality and informality has been widely documented, researchers have largely overlooked the features that lead to the thriving of informality. This study identifies these aspects through semi-structured interviews and participant observations with urban e-waste stakeholders in the Santiago Metropolitan Region of Chile. We discern six distinct working profiles (flea-market traders, scrap collectors, scrap dealers, scrapyard operators, collection-center managers, and treatment-company operators) that span a broad informality spectrum. From the characterization of the operations and labor aspects, we distill three key elements that determine the dominance of informality: agility (income-generation speed), capillarity (reach in the material collection), and flexibility (work-time adaptability). Our findings indicate that some profiles of the formal sector in the Santiago Metropolitan Region operate in a grey area with poor operational standards and a lack of contractual relationships, aligning them more closely with informality. We advocate for understanding and utilizing the features of informality to develop integration strategies and suggest a redefined understanding of formality in line with the diverse dimensions of vulnerability in the context of informality. While we identify potential opportunities to enhance a circular economy by embracing some of the advantages of the informal sector, future research should gauge the potential contributions of informality in terms of increasing collection and treatment rates and assess their environmental impact compared to formal services.